Therapeutic potential of naringin in improving the survival rate of skin flap: A review - Wang, Yincang; Li, Xiaodong; Lv, Hang; Sun, Lin; Liu, Bo; Zhang, Xiaofeng; Xu, Xilin (Frontiers in Pharmacology, 2023)
Naringin is the main component of Drynaria. Modern pharmacological studies have shown that naringin has a wide range of pharmacological activities, including antioxidant, anti-inflammatory, anti-apoptotic, anti-ulcer, and anti-osteoporosis effects. It is therapeutic in various clinical models such as atherosclerosis, cardiovascular diseases, diabetes, neurodegenerative diseases, and rheumatic diseases. This review investigates the pharmacological effects of naringin and its mechanism in improving flap survival, with an aim to provide a theoretical basis for its research in improving flap survival. This review will also provide a reference for future rational application of naringin.